Product Development by Additive Manufacturing and 3D Printer Technology in Aerospace Industry - (:unkn) unknown (My University, 2020)
The additive manufacturing and 3-dimensional manufacturing technology offer unparalleled flexibility in terms of part geometry, material composition and manufacturing time. There are many difficulties in manufacturing parts in the aerospace field. Thin-walled aircraft engine components and structures with complex geometry, the difficulties encountered in the processing of materials, are the other main factors that compel the aviation industry to adopt the use of layered manufacturing technology. It is progressing in the direction of radically changing the aerospace sector in the production of extremely complex and lightweight parts with material wastes that are almost none. The aerospace engine industry requires stronger, lighter and more durable components. Today's additive manufacturing technology provides new possibilities to meet these situations. In this study, research and development activities carried out in the field of layered manufacturing in the aviation industry have been examined and a literature review has conducted. In the experimental study, a scaled 3D prototype of an exemplary rocket equipment was produced using 3D printer technology. The manufacturing parameters of the study have been examined.

Katmanlı üretim ve 3 boyutlu üretim teknolojisi, parça geometrisi, malzeme bileşimi ve üretim süresi bakımından benzersiz bir esneklik sunar. Havacılık alanındaki parçaların imalatında birçok zorluklar vardır. Havacılık endüstrisinde, ince cidarlı uçak motoru bileşenleri, karmaşık geometriye sahip yapılar ve malzemelerin işlenmesinde karşılaşılan zorluklar katmanlı imalata yönelimi arttırmıştır. Son derece karmaşık ve hafif parçaların üretiminde kullanılan bu yöntem neredeyse hiç olmayan malzeme atıkları ile havacılık sektörünü kökten değiştirmek yönünde ilerliyor. Havacılık ve uzay endüstrisi, daha güçlü, daha hafif ve daha dayanıklı bileşenler gerektirir. Günümüzün katmanlı imalat teknolojisi bu durumları karşılamak için yeni olanaklar sunmaktadır. Bu çalışmada, havacılık endüstrisinde eklemeli imalat ile parça üretimi alanında yürütülen araştırma ve geliştirme çalışmaları incelenmiş ve literatür taraması yapılmıştır. Deneysel çalışmada, örnek bir roket ekipmanının ölçekli bir 3B prototipi 3B yazıcı teknolojisi kullanılarak üretilmiştir. Çalışmanın baskı parametreleri incelenmiştir.
Havacılık ve Uzay Endüstrisinde Katmanlı İmalat ve 3B Yazıcı Teknolojisi ile Ürün Geliştirme
Keywords: Mühendislik, Hava ve Uzay